Conditions in Reactive Systems and in Graph Rewriting - Koenig, Barbara (Electronic Communications of the EASST, 2012)
We introduce conditional reactive systems, by enriching the reactive systems of Leifer and Milner with application conditions. Furthermore we compare tothe situation in graph rewriting where application conditions play a major role.